Early Childhood Teachers' Perspective on The Implementation of Inclusive Education - Marwiyati, Sri (THUFULA, 2023)
The purpose of the study was to determine the views of early chilhood teachers and their preparation in implementing inclusive education in the city of Salatiga. This research method uses descriptive qualitative and field research. Data were obtained through interviews and questionnaires from early chilhood teachers in Salatiga City. The collected data is followed up with data reduction, data display and drawing conclusions. The results show that not all early chilhood teachers understand that Salatiga has declared itself as an inclusive city since 2012. The research data shows that some early chilhood teachers understand about inclusive education but they are not ready to accept children with special needs because they feel incapable in providing services, facilities, have special teachers for children with special needs, and do not yet have an inclusive curriculum so they are afraid that it will make the child's situation worse. The preparations needed by early chilhood teachers to implement PAUD inclusive schools are preparing facilities and infrastructure for learning for both children with special needs and normal children, preparing mature programs through mature inclusion curricula, preparing special teachers such as psychologists/special therapists and equipping teachers and parents in receiving and handling children with special needs through training activities. The success of inclusive education apart from the readiness of educational institutions is to change the public's understanding of children with special needs, children with special needs have the same rights as normal children so it is necessary to build cooperation with parents and the community to learn together to build inclusive schools.